Is a high level of general practitioner consultations associated with low outpatients specialist clinic use? A cross-sectional study - Deraas, Trygve S (BMJ Publishing Group, 2013)
OBJECTIVE: To examine if increased general practice activity is associated with lower outpatient specialist clinic use. DESIGN: Cross-sectional population based study. SETTING: All 430 Norwegian municipalities in 2009. PARTICIPANTS: All Norwegians aged ≥65 years (n=721 915; 56% women—15% of the total population). MAIN OUTCOME MEASURE: Specialised care outpatient clinic consultations per 1000 inhabitants (OPC rate). Main explanatory: general practitioner (GP) consultations per 1000 inhabitants (GP rate). RESULTS: In total, there were 3 339 031 GP consultations (57% women) and 1 757 864 OPC consultations (53% women). The national mean GP rate was 4625.2 GP consultations per 1000 inhabitants (SD 1234.3) and the national mean OPC rate was 2434.3 per 1000 inhabitants (SD 695.3). Crude analysis showed a statistically significant positive association between GP rates and OPC rates. In regression analyses, we identified three effect modifiers; age, mortality and the municipal composite variable of ‘hospital status’ (present/not present) and ‘population size’ (small, medium and large). We stratified manually by these effect modifiers into five strata. Crude stratified analyses showed a statistically significant positive association for three out of five strata. For the same three strata, those in the highest GP consultation rate quintile had higher mean OPC rates compared with those in the lowest quintile after adjustment for confounders (p<0.001). People aged ≥85 in small municipalities had approximately 30% lower specialist care use compared with their peers in larger municipalities, although the association between GP-rates and OPC-rates was still positive. CONCLUSIONS: In a universal health insurance system with high GP-accessibility, a health policy focusing solely on a higher activity in terms of GP consultations will not likely decrease OPC use among elderly.